The Comparison of the Energy Markets of the EAEU and the Scandinavian Countries: Best Practices for the Energy Integration - Perskaya, Victoria V. (International Journal of Energy Economics and Policy, 2019)
The development of the common energy markets and energy market innovations is a highly discussed topic, especially through the prism of the alternative energy. The Scandinavian countries are moving in both directions, at the same time, the EAEU countries are developing a single energy market, consisting of the four main sectors by the energy resource. The stages, pace and the institutional basis of the development of these two energy integration initiatives are different, due to similar climate conditions it is logical to suppose, they can be similar in some way. The article aims at comparing these energy markets, their dynamics, challenges and the possibility of institutional exchange. The main findings of the article include the proof that the comparison of the two markets by the financial and volume indicators is impossible, still institutional exchange is possible, moreover, enables them to solve several traditionally difficult problems. The practical importance of the article comprises the offered methodology of research through the developed synergy index, the recommendations for the EAEU and the Scandinavian countries. The novelty of the article is characterized by the institutional approach to the energy market, allowing to reveal its intrinsic characteristics – the energy flow between the institutional members and the regulative framework. Keywords: Energy markets, Scandinavia, EAEU, institutional development, development, energetic integration, recommendations JEL Classifications: P49; F02; O01 DOI: https://doi.org/10.32479/ijeep.8565